ECR-IoT: Energy-efficient and cluster-based routing method for WSN-based IoT using Harris hawk’s and whale optimization algorithms - Khalid A. Asaad; Saffer, Arkan A; Sarkawt H. Abdulqadir; Soran A. Pasha (Zanco Journal of Pure and Applied Sciences, 2024)
Internet of things (IoT) applications from home applications to military applications have been expanding day by day. Energy efficient routing schemes are vital for resource constraint wireless sensor networks (WSNs) and IoT. Clustering based routing scheme is one of the basic methods to extend the lifetime of WSN-based IoT. On the other hand, clustering is NP-hard problem and metaheuristic algorithms are suitable for clustering. In this paper, a new energy-efficient routing scheme is presented for IoT using two metaheuristic algorithms Harris hawk’s optimization (HHO) and whale optimization algorithm (WOA). The selection of the cluster header (CH) is based on the WOA using various parameters such as residual energy of nodes, distance to neighbors, distance to sink. After clustering phase, an energy efficient routing scheme was proposed using the HHO algorithm. The simulation results in MATLAB environment justifies that the proposed protocol improves network life by 10%, average energy consumption by 15%, packet delivery rate (PDR) by 12%, throughput by 11% and number of alive nodes by 15%.